A sequential method for preventive maintenance and replacement of a repairable single-unit system - Lai, K K; Leung, K N F; Tao, B; Wang, S Y (The Journal of the Operational Research Society, 2001)
This paper is concerned with when to implement preventive maintenance (PM) and replacement for a repairable 'single-unit' system in use. Under the main assumption that a 'single-unit' system gradually deteriorates with time, a sequential method is proposed to determine an optimal PM and replacement strategy for the system based on minimising expected loss rate. According to this method, PM epochs are determined one after the other, and consequently we can make use of all previous information on the operation process of the system. Also the replacement epoch depends on the effective age of the system. A numerical example shows that the sequential method can be used to solve the PM and replacement problem of a 'single-unit' system efficiently. Some properties of the loss functions W(L̄ n ,b̄ n ) and W̄ r (N) with respect to PM and replacement respectively are discussed in the appendix.